Recognizing First Nations Jurisdiction and Authority over Public Health for the Sioux Lookout First Nations Health Authority - Ariel Root; Natalie Hansen; Emily Paterson; Francine Pellerin; Lloyd Douglas; Janet Gordon (McMaster University Library Press, 2023)
Health outcomes for First Nations people living in community are challenged by the impacts of ongoing colonial laws, practices, and structures. First Nations control over developing community-led solutions is vital to improve overall wellbeing of First Nations people and communities. The Sioux Lookout First Nations Health Authority (SLFNHA) was established to develop health policy for the Sioux Lookout region, and to administer and oversee health services regionally. In 2016, SLFNHA implemented a First Nations-developed public health system, founded on traditional teachings and practices, called Approaches to Community Wellbeing. However, federal and provincial legal systems fail to recognize First Nations sovereignty over health and fail to address long-standing jurisdictional ambiguities. The COVID-19 pandemic has demonstrated the strength and resilience of the communities served by SLFNHA and their use of community-developed protocols and decision-making structures to keep their communities safe. SLFNHA supported the management of the COVID-19 pandemic within the communities it serves, despite not having access to the same tools, resources, information, and authority as the provincial health units. The pandemic also highlighted the public health inequities faced by First Nations in Ontario and failure of existing processes to recognize First Nations jurisdiction thereby continuing to impede the full implementation of a self-determined public health system as envisioned by First Nations leadership. Les résultats en matière de santé pour les membres des Premières Nations vivant dans la communauté sont affaiblis par les répercussions des lois, pratiques et structures coloniales en cours. Le contrôle des Premières Nations sur le développement de solutions communautaires est essentiel pour améliorer le bien-être général des peuples et des communautés des Premières Nations. La Sioux Lookout First Nations Health Authority (SLFNHA) a été créée pour élaborer une politique de santé pour la région de Sioux Lookout et pour administrer et superviser les services de santé à l'échelle régionale. En 2016, la SLFNHA a mis en place un système de santé publique développé par les Premières Nations, fondé sur les enseignements et pratiques traditionnels, appelé Approaches to Community Wellbeing. Cependant, les systèmes juridiques fédéral et provinciaux ne reconnaissent pas la souveraineté des Premières Nations sur la santé et ne clarifient pas les ambiguïtés de compétence qui ont existé de longue date. La pandémie de COVID-19 a démontré la force et la résilience des communautés desservies par la SLFNHA et leur utilisation de protocoles et de structures décisionnelles développés par la communauté pour assurer la sécurité de leurs communautés. La SLFNHA a soutenu la gestion de la pandémie de COVID-19 au sein des communautés qu'elle dessert, bien qu'elle n'ait pas accès aux mêmes outils, ressources, informations et autorité que les bureaux de santé provinciaux. La pandémie a aussi mis en évidence les inégalités en matière de santé publique auxquelles sont confrontées les Premières Nations en Ontario et l'incapacité des processus existants à reconnaître la compétence des Premières Nations, continuant ainsi d'entraver la mise en œuvre complète d'un système de santé publique autodéterminé tel qu'envisagé par les dirigeants des Premières Nations.